3D‐quantitative structure–activity relationship and docking studies of coumarin derivatives as tissue kallikrein 7 inhibitors. (23rd May 2017) - Zheng, Xin; He, Mengxi; Tan, Xiao; Zheng, Jun; Wang, Fangyu; Liu, Sen
Abstract: Objectives: Kallikrein 7 (KLK7) is a secreted serine protease that plays important roles in skin desquamation and tumour progression, which makes it an attracting drug target. To guide the design of KLK7 inhibitors, a series of coumarin‐based inhibitors were used to perform 3D‐quantitative structure–activity relationship analysis. Methods: 3D conformations of 37 inhibitors were generated and used to construct CoMFA and CoMSIA models. Then a complex model between the inhibitors and KLK7 was built with molecular docking. Key findings: With the training set, the CoMFA and CoMSIA models achieved q 2 values of 0.521 and 0.498, and r 2 values of 0.942 and 0.983, respectively. With the testing set, the predicted r 2 values were 0.663 and 0.669, respectively, for CoMFA and CoMSIA. 3D contour maps from these two models identified steric and hydrophobic interactions as the most important molecular features of these inhibitors. Furthermore, molecular docking study was performed to understand the binding modes between these compounds and KLK7, in which the critical steric and hydrophobic interactions between the inhibitors and KLK7 were confirmed. Conclusions: Steric and hydrophobic interactions are critical in the efficient binding of KLK7 inhibitors. Our analysis would provide a meaningful guideline for the rational design of novel KLK7 inhibitors.